Rates and types of hospitalisations for children who have subsequent contact with the child protection system: a population based case-control study. Issue 9 (23rd September 2009) - O'Donnell, M; Nassar, N; Leonard, H; Jacoby, P; Mathews, R; Patterson, Y; Stanley, F
Abstract : Objectives: To determine whether children who have child maltreatment allegation or substantiation have a higher rate of general hospital admissions and injury related admissions when compared to other children and to investigate other types of admissions, such as mental health, infections and admissions due to external causes. Study design: A prospective matched case-control study of children born in Western Australia between 1990 and 2005 using de-identified record linked Child Protection and Hospital Morbidity data. Rates of prior hospital admissions for cases versus controls were calculated, and conditional logistic regression was used to estimate the effect of hospital admission rate on the risk of child maltreatment allegation and substantiated allegation. Results: Children with child maltreatment allegations and substantiations had higher mean prior admission rates compared to controls. Higher rates of general admissions and admissions for injuries, infections, mental and behavioural disorders, and external causes of morbidity, were associated with a markedly increased risk of child maltreatment allegations and substantiation. Conclusions: The hospital system plays not only an important role both in the surveillance of maltreatment-related injuries and conditions but also in the role of prevention in the referral of families who may need support and assistance in ensuring the health and safety of their children. This research highlights the importance of moving to electronic patient records in identifying children who have high rates of admissions and the types of conditions they have previously presented with, particularly for injuries, mental and behavioural disorders and external causes of admissions.